Data for PhD dissertation "Sustainable rural electrification through community-managed mini-grids: Evidence from Tanzania" - Ngoti, Irene Fredolin (Medien- und Informationszentrum, Leuphana Universität Lüneburg, 2026)
This dataset consists of the data generated and analyzed for the PhD dissertation "Sustainable rural electrification through community-managed mini-grids: Evidence from Tanzania". It includes the interview guides and transcripts of (1) semi-structured interview (n=18) of Tanzanian village energy committee members, electricity users, technician(s), and village council leaders, (2) guide questions and transcripts of focus group discussions (n=4), and (3) coding files, i.e. code maps relations, codebook, coded segments and MAXQDA 24 memos. – The dataset only contains anonymized data excluding the original audio recordings due to data protection regulations.
Focus group / Group discussion
Transcription
Interview
Keywords: Kleinstnetz; Ländlicher Raum; Energieversorgung; Gemeinschaft; Partizipation; Stakeholder; Management; Energiepolitik; Nachhaltigkeit; Steuerungsprozesse; Tansania; Subsaharisches Afrika; Mini-grid; Rural Area; Energy Supply; Community; Participation; Stakeholder; Management; Energy Policy; Sustainability; Governance; Tanzania; Sub-Saharan Africa